Colloidal stability measurements of graphene nanoplatelets covalently functionalized with tetrahydrofurfuryl polyethylene glycol in different organic solvents - Shazali, Siti Shafiah; Amiri, Ahmad; Zubir, Mohd Nashrul Mohd; Rozali, Shaifulazuar; Zabri, Mohd Zakuan; Sabri, Mohd Faizul Mohd (Elsevier, 2018)
In this study, a facile, efficient, and cost-effective method was proposed for mass-production of tetrahydrofurfuryl polyethylene glycol-functionalized graphene nanoplatelets (TFPEG-treated GNPs) with improved colloidal stability in water and different organic solvents. In this method, zirconium(IV) oxychloride octahydrate was used as catalyst to covalently functionalize GNPs with TFPEG via direct esterification of carboxylic acid on the GNPs with the hydroxyl chains of TFPEG. Covalent functionalization was verified by Fourier transform infrared spectroscopy, Raman spectroscopy, and thermogravimetric analysis. Further, the morphology of the TFPEG-treated GNPs was determined via a high-resolution transmission electron microscopy. The stability of the treated GNPs in colloidal form was examined by dispersing 0.01 wt% of the solid sample into different organic solvents namely distilled water, methanol, ethanol, ethylene glycol, and 1-hexanol. It was found that the sedimentation rate of TFPEG-treated GNPs in distilled water, methanol, ethanol, ethylene glycol, and 1-hexanol was at 11, 25, 36, 18, and 47%, respectively, recorded after 15 days. Viscosity and thermal conductivity of water-based TFPEG-treated GNP nanofluids were also measured at different concentrations (0.100, 0.075, 0.050, and 0.025 wt%). The results suggest that these nanofluids have great potential for use as working fluids in industrial heat transfer systems.